A Comparative Analysis of Churna and Bhavita Churna of Stem Bark of Asoka – Saraca asoca (Roxb.) de Wilde through High Performance Thin Layer Chromatography - Ajayakumar, Ardra; Shincymol, V V; Ansary, P Y; Oommen, Sara Moncy (International Research Journal of Ayurveda & Yoga, 2021)
High performance thin layer chromatography is a powerful analytical technique used in the process of drug discovery. The fingerprint profile developed for each drug using this technique will be unique which makes it useful in establishing identity of a drug. The quality of different drug samples can be compared qualitatively and quantitatively through this technique. Asoka – Saraca asoca (Roxb.) de Wilde is a plant that has immense therapeutic potential. It is a drug which is significantly related to disorders of women. The stem barks are widely utilized for reproductive disorders like heavy and prolonged menstrual bleeding. The stem bark possesses several phytoconstituents including flavonoids, polyphenolics and sterols which accounts for its multiple beneficial action in therapeutics. The churna (powder) and bhavita churna (processed powder) of stem bark of Asoka – Saraca asoca (Roxb.) de Wilde was subjected to high performance thin layer chromatography and comparative analysis of different peaks were obtained. The number of peaks in the chromatogram of bhavita churna (processed powder) was more when compared to churna (powder) which substantiates its better potency.